SMU advances interdisciplinary education with new College of Graduate Research Studies - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The Singapore Management University (SMU) has today announced the establishment of its eighth school – the College of Graduate Research Studies (CGRS). The new College aims to develop world-class thought leaders who are trained to undertake cutting-edge research across disciplines, bringing about significant impact to businesses, societies and public institutions worldwide. To this end, the College will equip SMU postgraduate research students with knowledge and competencies to develop novel solutions that are relevant to some of today’s most challenging issues through the integration of disciplines, culture and industry. It will enhance integration and interdisciplinarity across the various SMU postgraduate research programmes that will enable our students to gain a holistic learning experience and well-grounded approach to their research. This will be achieved through interdisciplinary programmes, shared courses and professional training workshops. Furthermore, the College will strengthen networking, cohort building and collaborative opportunities for postgraduate research students across the various programmes, facilitated through the student and alumni groups.